2013
DOI: 10.1111/jace.12414
|View full text |Cite
|
Sign up to set email alerts
|

ZrO2/Dy2O3 Solid Solution Nano‐Materials: Tunable Composition, Visible light–Responsive Photocatalytic Activities and Reaction Mechanism

Abstract: A series of ZrO2/Dy2O3 solid solution nano‐materials with tunable compositions were successfully synthesized by the molten salt–assisted method. Structural characterization results show the positions, intensity, and width of the X‐ray diffraction peaks of products show a regular variation with increasing Dy3+ content which implies the gradually changes of crystal spacing and product size. In addition, all the products are single phase without the coexistence of zirconia and Dy2O3 further demonstrating the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…ZrO 2 /Dy 2 O 3 materials with tunable compositions have been synthesized and have exhibited good photocatalytic degradation performances over both RhB and MB under visible light irradiation, which result from their special defect structure, small crystal size, and large specic surface area. 123 Bi 2 -Mo x W 1Àx (x ¼ 0-1) solid solutions have exhibited high photocatalytic activity for the degradation of RhB under visible light, which was mainly attributed to the special structure of the solid solution and the lower energy band-gap. 124 The catalytic 126 Moreover, it has been shown that immobilizing palladium phthalocyaninesulfonate (PdPcS) integrated onto the FDU-15 mesopolymer provided a number of diamino groups inside the mesopores, which could be advantageous for excellent visible light photocatalytic activity and reusability.…”
Section: Modication Routes Towards Augmenting the Visible Light Resp...mentioning
confidence: 99%
“…ZrO 2 /Dy 2 O 3 materials with tunable compositions have been synthesized and have exhibited good photocatalytic degradation performances over both RhB and MB under visible light irradiation, which result from their special defect structure, small crystal size, and large specic surface area. 123 Bi 2 -Mo x W 1Àx (x ¼ 0-1) solid solutions have exhibited high photocatalytic activity for the degradation of RhB under visible light, which was mainly attributed to the special structure of the solid solution and the lower energy band-gap. 124 The catalytic 126 Moreover, it has been shown that immobilizing palladium phthalocyaninesulfonate (PdPcS) integrated onto the FDU-15 mesopolymer provided a number of diamino groups inside the mesopores, which could be advantageous for excellent visible light photocatalytic activity and reusability.…”
Section: Modication Routes Towards Augmenting the Visible Light Resp...mentioning
confidence: 99%
“…In this case usually the Bi-6s orbitals can hybridize with O-2p in VB. 9,28 It has been confirmed that in Bi-containing transition-metal (M) oxides, transition of the 6s electrons of Bi 3+ to the empty 3d orbitals of M 5+ can be possible depending on its structure, and its transition wavelength usually locates in a longer wavelength than the CT band in (M-O), that is, O 2À ?V 5+ in SrBi 3 VO 8 . This has been observed in the monoclinic BiVO 4 , 9 BiNbO 4 , and BiTaO 4 .…”
Section: August 2015mentioning
confidence: 98%
“…It is well‐known that optical absorption energy is decided by the band gap, which is followed by the release of holes and electrons from the valence (VB) and the conduction (CB) bands, respectively. To get photocatalysts with effective response in visible light wavelength, it is necessary to narrow the band‐gap of the semiconductors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technological use of ZrO 2 with visible light was improved by several surface modification methods including metal doping [17,18], coupling with other semiconductors [19][20][21], and modification with carbon [22]. Du et al [23] studied the photocatalytic activity of ZrO 2 /Dy 2 O 3 nano-materials for the degradation of rhodamine-B under visible light. Ma et al [24] evaluated the photocatalytic activity of TaON modified ZrO 2 nanoparticles for the production of hydrogen under visible light.…”
Section: Introductionmentioning
confidence: 99%